A STUDY ON THE ABILITY OF FIRST YEAR STUDENTS OF ENGLISH DEPARTMENT FKIP UR IN USING ADJECTIVE ORDER - ', Musdalifa; ', Erni; ', Syafri K (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The aim of this study is to find out the ability level of first year students of English Department FKIP UR in using adjective order. This research was done to answer the research question; what is the ability level first year students of English Department FKIP UR in using adjective order. The design of this research is descriptive research which used quantitative data, where the students were assessed by their score. This research used written test as instrument which consisted of 40 questions. The population of this research is all of first year students of English Department FKIP UR in academic year 2016/2017 with the total is 120 students and there were 30 students were selected as the sample of this research by using cluster random sampling technique. The finding of this research showed that the ability level of first year students of English Department FKIP UR in using adjective order is categorized into average level with the mean score 53.1.Key Words: Ability, adjective order